Early predictors of neonatal hyperbilirubinemia in full term newborn - May Ahmed Khairy; Walaa Alsharany Abuelhamd; Ismail Mohamed Elhawary; Ahmed Said Mahmoud Nabayel (Elsevier, 2019)
Background: Reliable predictive markers enabling physicians to identify which newborns will develop significant hyperbilirubinemia have become mandatory for prevention of severe hyperbilirunemia. We aimed at determining the critical cord serum bilirubin and albumin levels and bilirubin/albumin ratio early as reliable markers. Study design: This prospective study included 175 full-term neonates. Measurement of cord bilirubin, albumin and bilirubin/albumin ratio was done to predict significant hyperbilirubinemia in healthy term newborns based on serum bilirubin measurements made within 5 days of life. Results: Most cases that developed significant neonatal hyperbilirubinemia (67.9%) had cord albumin level ≤ 2.8 gm/dl. Cord Bilirubin/albumin ratio cut off value > 0.61 had a good predictive value with a sensitivity of 100% and specificity of 88.4%, and cord serum albumin cut off value ≤ 3.0 mg/dl also had a good predictive value with a sensitivity of 85.7% and specificity of 67.3%.ROC curve analysis of cord total bilirubin demonstrated that a cut off value of ≥1.84 mg/dl had a good predictive value with a sensitivity of 100.0% and specificity of 87.1%. Conclusion: Cord bilirubin/albumin ratio, serum bilirubin and albumin could be early predictors for neonatal hyperbilirubinemia. Key Words: cord bilirubin/albumin ratio, cord serum albumin, cord serum bilirubin, neonatal hyperbilirubinemia